(untitled) (Communication & Society, 2023)
This study explores the specific characteristics of science news stories posted on social media platforms during the first phase of the global pandemic crisis (the first semester of 2020). The focus of the study is to enhance our understanding of the selection criteria for science-related news content posted on social media platforms. Our approach takes into consideration the evolving technological environment of these platforms and the new relationships between media professionals and social media users. Our findings indicate that, under specific circumstances, scientific discoveries may be prioritized in the selection of news stories. We also suggest specific additions to the framework proposed by Harcup and O’Neil (2017), indicating that news stories during crisis situations are more internationally oriented, where audience proximity is created not around “nearby” events but those occurring in other countries around the world. In times of crisis, the main target of news stories is not simply to attract the audience’s interest with classic clickbait tactics but to respond to the immediate socio-political context in a meaningful way.